ANALISIS STABILITAS HASIL DENGAN MODEL EBERHART-RUSSELâS DAN BIPLOT PADA UML JAGUNG QPM - Gaffar, M.Yasin Hasanul; Santoso, Sigit Budi; Sunarti, Sri (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2012)
Sta bility is one of the statist ical model for desirable properties to released a variety under wide cul tivat ion. The m odel of Eberhart -Russelâs and Biplot ha s been applied t o ana lyze of QPM as candidate new ICERI (Indonesian Cereals Research Institute) variety, there are 14 genotypes F1 (single cross) fr om in bred lines S3-S4 of populat ion MSQ.K1C0 x tester MR14Q an d 2 opv. (open pol linat ed var iety) were conducted in seven environment un der central maize production in Indonesi a i.e. Sout h Sul awesi (Mar os e1, Bajeng-Gowa, e2), Central Sulawesi (Donggala, e3), East Java (Muneng-Probol ingg, o, e4), South Ka liman tan (Ba njarba ru, e5, and Pala ihari, e6), and Riau (Pakanbaru, e7). QPM is high lysine and tryptophane in endosperm maize. The exper iment in each environment wer e con ducted by r cbd (r andomi zed complete block design) with four replication in rainy sea son 2007, t he sta bilit y to studied by Eberha rt-Russelâs with mode l Y ij =Î¼+Î²iIj+Î´ij, iï¹j(Y: yiel d,Î¼:mean,Î²:regression coeffi cien t, I: envir onmen tal index and : Î´0,=Î£Ij deviation from regression), and sta bilit y par ameter j2jii/IIY=bï,df of pool eddeviation and pooled err or computed by g(e-2)=80 and eg(r-1)=336, g: 16 of candidate QPM, e:7 environments. The result source of variation by rcbd that ther e are signi ficant of genotypes in all environm ents a nd in pool ed an alysi s by E berha rt-Russelâs were founded in teraction of gxe as significant. In bi plot x, y shown that single cr oss MSQ.K1C0.61-1-1xMR14Q was stable genotypes in seven environm ent an d could be recom mended as new candi date hybrids with aver age yi eld 6.673 t/ha. Positive inter action effect was founded on three candidate hybrids MSQK1C0.8-1-1xMR14,MSQ.K1C0.22-1-1xMR14Q, and MSQ.K1C0.61-1-1x MR14Q in Muneng-Pr obolin ggo, Donggala, and Banjarbaru. with yielded 5.384-6.988 t/ha.